The Mediating Role of Profit Management Between Capital Structure and Financial Performance in Manufacturing Companies Registered on BEI for the 2019-2023 Period - Rauhar, Syehlin; Mansyuri, M. Ikhwan; Asmawati, Asmawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
By manufacturers listed in the Indonesian Stock Exchange (IDX) from 2019 to 2023, this consider examines how capital structure influences money related execution. The purposive inspecting strategy was utilized to choose the investigate test, which included 505 money related explanation information and 101 companies. The examination comes approximately show up that benefit organization as measured by optional collections (DA) isn't through and through impacted by capital structure as measured by debt-to-equity extent (DER). This shows that the level of obligation does not influence This demonstrates that management's decision to actualize profit administration hones isn't impacted by the level of obligation; on the inverse, the capital structure turns out to have a positive and critical influence on budgetary execution measured utilizing Return on Assets (ROA), illustrating that companies can utilize commitment to amplify In expansion, advantage organization as well turns out to have a positive impact on monetary execution, laying out that.